Modification of polymers to synthesize thermo-salt-resistant stabilizers of drilling fluids - Artykova Zhadyra; Beisenbayev Oral; Issa Aziza; Kydyraliyeva Aigul (Open Engineering)
This study focuses on the modification of polymers to synthesize thermo-salt-resistant stabilizers for drilling fluids. The objective is to enhance the thermal and salt resistance of industrial drilling fluids, properties that cannot be achieved through standard homogenization techniques. The research investigates the introduction of sulfonic acid and hydrophobic groups into polymer chains to regulate the rheological properties of drilling fluids. The synthesis involves copolymerization of acrylonitrile and vinyl sulfonic acid in an aqueous medium using potassium persulfate and sodium sulfate as initiators. The process consists of two stages: polymerization under controlled conditions and further hydrolysis and modification of polyacrylonitrile using sodium hydroxide, sulfuric acid, fatty acids, and formalin. The study examines the impact of pH, temperature, and initiator concentration on the yield, composition, and structure of the resulting copolymers. The results indicate that the optimal ratio of acrylonitrile to vinyl sulfonic acid is 80:20 at pH 3–6, which, combined with hydrolysis and modification, produces composite multifunctional polymer stabilizers with amide, imide, carboxylate, and sulfonic groups. These stabilizers exhibit enhanced hydrophilicity and an amorphous structure, making them effective for use in extreme drilling conditions. The synthesized multifunctional polyelectrolytes, containing sulfonic and sulfomethylated groups, demonstrate improved thermal and salt resistance, ensuring the stability and performance of drilling fluids under harsh conditions.